2020
DOI: 10.1097/ju.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Positron Emission Tomography/Computerized Tomography in Assessing Tumor Burden in Prostate Cancer Nodal Recurrence: Head-to-Head Comparison of 68 Ga-PSMA and 11 C-Choline in a Large, Multi-Institutional Series of Extended Salvage Lymph Node Dissections

Abstract: Introduction. The aim of the study was to compare 11 C-Choline and 68 Ga-PSMA in men undergoing SLND for nodal recurrent PCa.Materials and Methods. The study included 641 patients who experienced PSA rise and nodal recurrence after radical prostatectomy and underwent SLND. Lymph node recurrence was documented by PET/CT scan using either 11 C-Choline (n=407; 63%) or 68 Ga-PSMA ligand (n=234; 37%). The outcome was underestimation of tumour burden (difference between number of positive nodes on final pathology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…29,30 Moreover, all patients in our series were staged using conventional imaging, due to the limited availability of prostate-specific membrane antigen positron emission tomography/computed tomography (PSMA PET/CT) at the time of study enrollment. [31][32][33] Indeed, several studies have demonstrated the superiority of PSMA PET/CT over conventional imaging in staging QUHAL ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Moreover, all patients in our series were staged using conventional imaging, due to the limited availability of prostate-specific membrane antigen positron emission tomography/computed tomography (PSMA PET/CT) at the time of study enrollment. [31][32][33] Indeed, several studies have demonstrated the superiority of PSMA PET/CT over conventional imaging in staging QUHAL ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Though molecular imaging with Choline or PSMA PET/CT has substantially improved detection rates up to 76% for PSA values <1 ng/ml (17), we probably still underestimate the true extent of disease. In a very recent study by Fossati et al the number of positive lymph nodes found on histology exceeded the number of PET/CT positive lymph nodes (18). This effect was less pronounced for PSMA-than for Choline -PET.…”
Section: Discussionmentioning
confidence: 86%
“…In a very recent study by Fossati et al. the number of positive lymph nodes found on histology exceeded the number of PET/CT positive lymph nodes ( 18 ). This effect was less pronounced for PSMA—than for Choline—PET.…”
Section: Discussionmentioning
confidence: 94%
“… Distant metastasis (any metastasis that is not local or regional) Distant metastases associated with worse OS and visceral metastases more than bone metastases [47] ; distant metastases associated with worse CSS than local metastases or nonmetastatic cancer [45] Neither older nor more recent noninvasive mPC imaging methods have been fully integrated with longitudinal precision medicine trials to date. Comparisons of digital bone scan [48] , PET CT [49] , whole-body MRI [50] , and other methods are needed. Integrated studies of these methods in trials of stereotactic ablative radiotherapy of individual metastases [51] are needed.…”
Section: Resultsmentioning
confidence: 99%